Advanced Stage Hepatocellular Carcinoma with Multiple Metastasis and Vascular Thrombosis: A Case of Complete Response to Sorafenib - Simão, Adélia (2016)
Sorafenib is a multi-targeted tyrosine kinase inhibitor, with antiangiogenic and antiproliferative properties, approved for the treatment of advanced hepatocellular carcinoma. It induces a significant increase in the median overall survival, despite a complete response to treatment being rare. We report a clinical case of a 60-year-old male with hepatic cirrhosis, Child-Pugh class A and performance status 0, and advanced hepatocellular carcinoma. The primary tumor measured 17 x 8 cm and had diffuse intrahepatic metastization, extensive lung and left adrenal invasion, as well as thrombosis of inferior vena cava, with projection to the right atrium. This patient showed a rapid and complete response to sorafenib, evaluated by mRECIST (modified Response Evaluation Criteria in Solid Tumors), that remains after three years of treatment.